2019
DOI: 10.4038/vingnanam.v14i1.4139
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Thondaimanaru Barrage Construction on socio – economic status of fishing communities in Thondaimanaru Lagoon, Jaffna, Sri Lanka

Abstract: Present study was conducted to determine the impacts of barrage construction on livelihood status of fishers who involve fishing in Thondaimanaru lagoon. The data related to the socio -economic condition of fishers in the particular area were obtained through a pre -tested structured questionnaire and in -depth guided interviews from July 2016 to January 2017. Randomly selected 25 fishermen were interviewed. The collected data were subjected to descriptive statistical analysis. Survey results indicated that 88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Socio-economic characteristics of the respondents Socio -economic status is a measure of an individual's or family's economic and social position in relation to others, based on various variables responsible for that like income, education, occupation, family effluence, physical assets, social position, social participation, caste, muscle power, political influence, etc. (Shobiya et al, 2019). General details such as ethnicity, gender, age, family size, education, occupational patterns and income generation were investigated in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Socio-economic characteristics of the respondents Socio -economic status is a measure of an individual's or family's economic and social position in relation to others, based on various variables responsible for that like income, education, occupation, family effluence, physical assets, social position, social participation, caste, muscle power, political influence, etc. (Shobiya et al, 2019). General details such as ethnicity, gender, age, family size, education, occupational patterns and income generation were investigated in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…These may be the reasons for refraining from accomplishment of good education at their young ages. It can be compared with similar studies conducted around Jaffna peninsula, where the literacy rate of fisherwomen was found to be lower than the fishermen (Ragavan, et al, 2017;Tharmine, et al, 2018;Shobiya, et al, 2019).…”
Section: B Literacy Rate Of Fisher Womenmentioning
confidence: 93%
“…The water for the turbidity, nitrate, and phosphate analyses was taken from the sample bottles within 24 hours of sampling. The physical parameters such as air and water temperature, pH, salinity, Total Dissolved Solid (TDS), Electric Conductivity (EC), and Dissolved Oxygen (DO) were measured onsite using the smarTROLL multiparameter (In-situ 458389, USA) [9]. BOD was measured by Winkler's method (APHA, 1998).…”
Section: Methodsmentioning
confidence: 99%